2014
DOI: 10.1007/s10067-014-2666-3
|View full text |Cite
|
Sign up to set email alerts
|

Heart involvement in systemic sclerosis: a combined echocardiographic and scintigraphic study

Abstract: The aim of this study is to investigate systemic sclerosis (SSc) patients without clinically evident heart disease for cardiac abnormalities. SSc patients and age- and sex-matched healthy controls from the hospital staff underwent transthoracic echocardiography for the assessment of the left ventricle (LV) morphology and function and estimation of the pulmonary artery systolic pressure (PASP). Patients further underwent stress-rest myocardial perfusion imaging (MPI) scintigraphy by single-photon emission compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Among 22 patients with scleroderma and pulmonary interstitial disease who had a pulmonary histology, 64% had a NSIP pattern and 36% a UIP pattern, with a median survival of 15 versus 3 years, respectively [14]. The presence of an extensive pulmonary fibrosis, defined by lesions extent above 20% on high resolution-CT scan and/or FVC below 70%, was associated with a 5-year mortality rate of 60% [15].…”
Section: Pulmonary Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 22 patients with scleroderma and pulmonary interstitial disease who had a pulmonary histology, 64% had a NSIP pattern and 36% a UIP pattern, with a median survival of 15 versus 3 years, respectively [14]. The presence of an extensive pulmonary fibrosis, defined by lesions extent above 20% on high resolution-CT scan and/or FVC below 70%, was associated with a 5-year mortality rate of 60% [15].…”
Section: Pulmonary Involvementmentioning
confidence: 99%
“…Myocardial damages are most often linked to ischemic injury associated to disorders of the coronary microcirculation that may lead to myocardial fibrosis. Up to 60% of patients showed perfusion defects on myocardial scintigraphy [15]. In a large international series of 3,656 SSc patients, 24-27% of patients had palpitations, 11-13% a conduction block, 15% a diastolic dysfunction and 5% a reduced left ventricular systolic function [6].…”
Section: Heart Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, myocardial scintigraphy is also useful for detecting cardiac lesions. Papagoras et al 336 . reported that reduced blood flow was found on stress myocardial perfusion scintigraphy in 60% (21/35) of asymptomatic SSc patients, and scintigraphy is considered useful for the early diagnosis of myocardial damage that is caused by SSc.…”
Section: Guidelines For Treatment Of the Heartmentioning
confidence: 99%
“…335 Therefore, myocardial scintigraphy is also useful for detecting cardiac lesions. Papagoras et al 336 reported that reduced blood flow was found on stress myocardial perfusion scintigraphy in 60% (21/ 35) of asymptomatic SSc patients, and scintigraphy is considered useful for the early diagnosis of myocardial damage that is caused by SSc. Only a limited number of facilities are able to implement MRI and myocardial perfusion scintigraphy, but implementing these tests in the available facilities is recommended.…”
Section: Recommendation Level: 2cmentioning
confidence: 99%